Kepemimpinan Digital dan Ekonomi Sirkuler UKM Tenun untuk Pencapaian SDGs - Karolus Wulla Rato; Roswita Sari; Noviana Martha Dimu; aulino Lucky Puty (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to analyze the influence of digital leadership, digital transformation, and circular economy practices on the economic performance of weaving SMEs and their contribution to the achievement of the Sustainable Development Goals (SDGs). This study employed a quantitative approach with an explanatory research design. Data were collected from 98 weaving SME owners or managers through questionnaires and analyzed using validity testing, reliability testing, classical assumption tests, and linear regression analysis. The findings show that digital leadership has a positive and significant effect on the economic performance of weaving SMEs. Digital transformation also has a positive and significant effect by expanding market access, improving operational efficiency, and strengthening customer relationships. In addition, circular economy practices have a positive and significant effect through resource efficiency, production waste reduction, and the creation of added value from residual materials. These findings indicate that the integration of digital leadership, digital transformation, and circular economy practices is a strategic approach to enhancing the competitiveness of weaving SMEs while supporting the achievement of the SDGs. This study contributes to the development of cultural-based SME studies by positioning digitalization and sustainability as key foundations for strengthening local economic performance.